Time prediction of serial criminals based on commensurability. Issue 4 (3rd July 2016) - Feng, Lichao; Hao, Shengnan; Zhao, Yongsheng; Zhang, Chunyan
Abstract: Twisted souls and antisocial spirits have resulted in serial criminals. In order to prevent such crimes which cause great harm to public security, the paper has established a kind of quickly and effective scheme to help the policemen to arrest the criminals based on commensurability theory. Taking the criminal of "Yorkshire Ripper" as an example, we compile the procedures of commensurability of ternary, quaternion and quintuple of his criminal time. And the model is very accurate because the predicted value based on the commensurability theory equals to the actual value. When facing others serial criminals, commensurability theory can also be applied to predict the possible coming criminal time using the time of past criminals. Obviously, the scheme we established is also helpful to build a harmonious society.